Students’ Perceptions in Using Edlink in Supporting 21st Century Skills Learning - Riwu Ratu, Martinus; Beatrice Sogen, Maria Magdalena; Jelita, Felisa; Kuman, Jennet Chrysmichael Elizabeth (JUPE : Jurnal Pendidikan Mandala, 2025)
Online learning has become an urgent necessity in current education, especially during the COVID-19 pandemic. The Sevima Edlink application is an educational platform that offers various features to support the online learning process. This research aims to evalute student’s perceptions of using Edlink in supporting 21st – century skills learning among students of the Faculty of Teacher Training and Education, Universitas Citra Bangsa Kupang (FKIP UCB). Through a case study approach, data was collected via questionnaires from FKIP UCB students who use the Sevima Edlink application. The research results indicate that the use of the Sevima Edlink application. The research results indicate that the use of the Sevima Edlink application significantly supports 21st – century skills learning. This application helps facilitate easy access to learning materials, interaction between lecturers and student, collaboration among students, as well as quick assesment and feedback. Although there were some technical challenges faced by students, the benefits gained from using the Sevima Edlink application positively contributed to improving their online learning experience. This research provides valuaable insights for educational institutions in utilizing educational applications to support 21st – century skills learningg. Pembelajaran daring telah menjadi kebutuhan mendesak dalam pendidikan saat ini, terutama selama pandemi COVID-19. Aplikasi Sevima Edlink merupakan platform pendidikan yang menawarkan berbagai fitur untuk mendukung proses pembelajaran daring. Penelitian ini bertujuan untuk mengevaluasi persepsi mahasiswa dalam menggunakan edlink dalam mendukung pembelajaran keterampilan abad ke-21 pada mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Citra Bangsa Kupang (FKIP UCB). Melalui pendekatan kasus, data dikumpulkan melalui angket kuesioner dengan mahasiswa FKIP UCB yang menggunakan aplikasi Sevima Edlink. Hasil penelitian menunjukkan bahwa penggunaan aplikasi Sevima Edlink secara signifikan mendukung pembelajaran keterampilan abad ke-21. Aplikasi ini membantu memfasilitasi akses mudah ke materi pembelajaran, interaksi antara dosen dan mahasiswa, kolaborasi antar mahasiswa, serta penilaian dan umpan balik yang cepat. Meskipun terdapat beberapa tantangan teknis yang dihadapi oleh mahasiswa, manfaat yang diperoleh dari penggunaan aplikasi Sevima Edlink memberikan kontribusi positif dalam meningkatkan pengalaman belajar mereka secara daring. Penelitian ini memberikan wawasan yang berharga bagi institusi pendidikan dalam memanfaatkan aplikasi pendidikan untuk mendukung pembelajaran keterampilan abad ke-21.